Fiction and pragmatics - Locher, Miriam A.; Jucker, Andreas H.; Landert, Daniela; Messerli, Thomas C. (Elements in pragmatics, 2023)
This volume outlines current issues in the study of the pragmatics of fiction. It starts from the premise that fictional texts are complex and multi-layered communicative acts which deserve attention in pragmatic research in their own right, and it highlights the need to understand them and to explore pragmatic effects and pragmatic theorising.